Cognitive reorganization and protective mechanisms in pregnancy and the postpartum period - Anderson, Marla V. (My University, 2011)
A clear picture describing cognitive change in pregnant women has yet to emerge. Recent work investigating pregnancy-induced cognition in women focuses on memory deficits, in contrast to the cognitive advantage and neural plasticity described in the nonhuman literature. The following thesis reviews the literature investigating pregnancy-induced cognitive change, and then reports three empirical studies investigating cognition in pregnant and postpartum women. I hypothesized that, given the high stakes associated with pregnancy and the postpartum period, adaptive mechanisms designed to keep the mother safe exist in the cognitive domain, in much the same way that Nausea and Vomiting in Pregnancy is now believed to buffer the mother and fetus from harm. The results of a meta-analysis and a longitudinal study comparing cognitive performance in pregnant and non-pregnant women suggest that there are cognitive costs associated with becoming a mother, in both pregnancy and the postpartum period. Recent research suggests that pregnant women possess an advantage in processing social stimuli: I report that pregnant women show facilitated recognition of faces. Finally, I examined nesting, and developed a questionnaire that tracked women through pregnancy and into the postpartum period, comparing non-pregnant women at similar time points. I report that nesting peaks in the third trimester, and involves space preparation and social withdrawal. Reproductive state affects cognition in ways that are distinct, and perhaps specialized, including a deficit in some areas (processing speed), and a cognitive advantage in others (face recognition), some of which may serve a protective function.
Keywords: Pregnancy; cognition; recognition; nesting; adaptationist; threat; Cognitive Psychology; Psychology; Social and Behavioral Sciences; Cognitive Psychology